Philosophical Thoughts of Ibn Sina - M Hamdan Ramadhan; Maspuroh; Kurnia Ripah; Nia Nuraeni; Santi Susanti (Penerbit Hellow Pustaka, 2025)
Ibnu Sina is an important Muslim philosopher who built the theory of Prophethood with his treatise Itsbat al-Nubuwat. He marks the pinnacle of the Islamic philosophy with his thoughts on paripathetic philosophy, known as Masya'i, the syncretic philosophy (synthetic from the teachings of Revelation, Islam, Aristotelianism and Neoplatonism). Like other philosophers, Ibn Sina is a Muslim philosopher whom some criticized only as a duplication of Hellenism (Greek philosophy), which does not reflect Islamic thought. Yet those who gave birth to Islamic philosophy and strive and successfully combine revelation with reason, creed with wisdom, religion with philosophy. That explains to man that revelation is not contrary to reason. Ibn Sina makes a final synthetic of Islam with the philosophy of Aristotelianism and Neoplatonism into a permanent intellectual dimension in the Islamic world and endures as a philosophical teaching that lives to this day. Ibn Sina is a perfect digger and eternal translator of paripathetic philosophy which shows up to the philosophical gates of the illumination theosophy which signifies integral integral integration of philosophy and spirituality. One and a half centuries after the Philosophy of masya'i he brought Shihabuddin Suhrawardi to the illumination philosophy (al-ishraq).